Study and Evaluation of the Medium Density Fiberboard Made From Old Newspaper - Jaber, Mohammed Ali (Al-Qadisiyah Journal of Pure Science, 2017)
Research includes Technology for the production of medium -density fiber board made from old newspaper and finding the best conditions for the manufacture of the fiber board and the required specifications. was reached methods produced industrially. The research aims to study was effect of newspaper fiber mixed with cement and polymer blend (poly vinyl estate with MDI) and the press time 10 min on the properties of MDF panels were determined. Physical properties (thickness swelling, water absorption) and mechanical properties (Bending modulus of rupture and compressive strength) of the panels were determined according to the procedure of ASTM standards . This study showed reduction in bending modulus and increased the compressive strength of the panels as cement was loaded from 10 to 40%. Thickness swelling and water absorption of MDF panels was decreased with addition of cement to the panels